Coastal Community Health Behavior: Implementation of the 7 Pillars of the Healthy Living Community Movement (Germas) - Muria Herlina (International Journal of Science and Society, 2019)
The purpose of this study was to determine the implementation of the 7 pillars of the healthy living community movement (Germas) in-depth and comprehensively. The research location was in Kampung Melayu Sub-District, a coastal area of ​​Bengkulu City. This research method uses qualitative and quantitative approaches or joint research and uses techniques in one phase/research period. Data collection was carried out by using questionnaires to 125 respondents. Qualitatively obtained 17 informants through the sample aims, data collection through in-depth interviews, observation, and FGD, using matrix table analysis. The results of the study based on statistical tests found that 6 variables with p-values> 0.05, namely father's education, mother's education, highest education in the family, ethnicity, rheumatism / joint pain, and vision. The results of in-depth interviews show that the most difficult behavior to change is the behavior to stop smoking because it has become a habit, it is not usual to regularly check the health and eating fruit has not been a priority, and daily work is assumed to be doing physical activity.